2018
DOI: 10.1002/celc.201801240
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of a Highly Active 3‐Dimensional Fe−Nx−CNTs/rGO Composite Catalyst for Oxygen Reduction

Abstract: A facile one‐pot method to synthesize a Fe−Nx−CNTs/rGO catalyst by using melamine and FeCl2⋅4H2O as low‐cost precursors is reported.The 3‐dimensional porous structure and the dispersion of precursor were completed at the same time. Suitable precursor and concentration selection not only solved the aggregation of graphene but also improved its effective iron content and activity. The obtained catalysts exhibited oxygen reduction activitycomparable to commercial Pt/C with a half‐wave potential (the potential whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…57 Fe Mössbauer spectroscopy has proven to be a powerful technique for identifying the coordination environments, oxidation and spin states of Fe atoms in iron complexes. 60 Important information for the electronic properties of active sites in catalysts 61,62 and insights into the mechanisms involved for the catalytic process can be obtained. 63,64 Mössbauer spectroscopy and its deconvolution for all six iron complexes are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…57 Fe Mössbauer spectroscopy has proven to be a powerful technique for identifying the coordination environments, oxidation and spin states of Fe atoms in iron complexes. 60 Important information for the electronic properties of active sites in catalysts 61,62 and insights into the mechanisms involved for the catalytic process can be obtained. 63,64 Mössbauer spectroscopy and its deconvolution for all six iron complexes are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed preparation procedures for rGO can be found in the Supporting Information. The Fe–N–C catalysts were obtained following previous studies. ,, FeCl 2 ·4H 2 O and melamine were added dropwise to the GO and rGO dispersion solutions, respectively. After full stirring, the mixture was freeze-dried to form a 3D porous structure, followed by pyrolysis at 750 °C for 3 h under argon and ammonia (5 v. % in Ar) flows to form Fe–N–C active sites on the supports.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Since then, numerous M–N 4 macrocycles, such as phthalocyanines, tetraazaannulenes, and porphyrins, have been intensively investigated. Subsequently, researchers found that high-temperature pyrolysis methods can significantly improve the activity and stability of these carbon-based macrocyclic-derived catalysts . As an alternative strategy, M–N–C catalysts have been prepared and exploited in recent decades by direct pyrolysis of common inorganic salts, nitrogen precursors, and carbon carriers, which observably improved the catalytic performance. In addition, great progress was also achieved in metal–organic frameworks as effective precursors to yield atomically dispersed and nitrogen-doped single-metal active sites. Among these sources of metals, Fe is the most active species used for M–N–C catalysts in the ORR and iron–nitrogen (FeN 4 ) coordination sites have emerged as the most promising NPMCs for FCs, followed by Co and Mn. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the aim of replacing expensive Pt catalysts, an increasing number of non-platinum catalysts have been explored [31][32][33][34]. However, the development of non-platinum catalysts relies on an in-depth understanding of their active sites and pathways.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%